2012
DOI: 10.1088/0953-8984/24/19/195801
|View full text |Cite
|
Sign up to set email alerts
|

Self-trapping of single and paired electrons in Ge2Se3

Abstract: We report the theoretical prediction of single and paired electron self-trapping in Ge(2)Se(3). In finite atomic cluster, density functional calculations, we show that excess single electrons in Ge(2)Se(3) are strongly localized around single germanium dimers. We also find that two electrons prefer to trap around the same germanium dimer, rupturing a neighboring Ge-Se bond. Localization is less robust in periodic, density functional calculations. While paired electron self-trapping is present, as shown by wave… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 49 publications
1
9
0
Order By: Relevance
“…In fact these features of the PDOS are strikingly similar to those of the single STE in the cluster calculations (see Figure 3 (a) in Ref. [5].) Taken together, the atomic relaxations and the electronic structure of the neutral interstial silver atom imply that in this bulk crystalline model, an isolated silver atom autoionizes, becoming Ag +1 , and the excess electron self-traps around a germanium pair.…”
Section: Neutral Interstitial Ag and Snsupporting
confidence: 73%
See 4 more Smart Citations
“…In fact these features of the PDOS are strikingly similar to those of the single STE in the cluster calculations (see Figure 3 (a) in Ref. [5].) Taken together, the atomic relaxations and the electronic structure of the neutral interstial silver atom imply that in this bulk crystalline model, an isolated silver atom autoionizes, becoming Ag +1 , and the excess electron self-traps around a germanium pair.…”
Section: Neutral Interstitial Ag and Snsupporting
confidence: 73%
“…We have shown that STE's are bound to either Ge-Ge or Sn-Ge dimers. This should persist in non-crystalline material because these dimers form the bottom of the conduction band [5]. We have also shown that both Sn and Ag autoionize upon entering Ge 2 Se 3 .…”
Section: Discussionmentioning
confidence: 73%
See 3 more Smart Citations